Random amplified DNA polymorphism of almond (Amygdalus communis L.) cultivars in Apulia - Resta P.; Ferrara G.; Fanizza G.; Palasciano M.; Godini A. (X GREMPA Seminar, 1998)
The more than 100 almond cultivars grown in Apulia (South Italy) could be a source of genetic variation adapted to the Mediterranean environment, provided that a proper classification, identifying similar characteristics and synonymous cultivars, is made. DNA-based assays could integrate traditional classifications based on morphology. In the comparison of 17 Apulian almond cultivars, by random amplification of their DNAs (RAPD) with 60 primers, 418 bands were detected, of which 241 were polymorphic (57.7 per cent). Primers distinguishing the majority of the tested cultivars were found. Cultivar relationships were estimated through cluster analysis (UPGMA) based on RAPD data. High similarity between two pairs of cultivars was revealed, and was in agreement with previous observations. Only tentatively, two additional aggregations were suggested. RAPDs seemed to be effective classification tools for germplasm conservation and breeding.
10. GREMPA Seminar, 1996/10/14-17, Meknès (Morocco)